Bioethanol production from sodium hydroxide/hydrogen peroxide-pretreated water hyacinth via simultaneous saccharification and fermentation with a newly isolated thermotolerant Kluyveromyces marxianu strain. (October 2015) - Yan, Jinping; Wei, Zhilei; Wang, Qiaoping; He, Manman; Li, Shumei; Irbis, Chagan
Highlights: H2 O2 /NaOH pretreatment of water hyacinth at mild conditions is effective. A newly isolated K213 showed higher ethanol production from glucose at 42 °C. K213 strain was identified as Kluyveromyces marxianu. K213 by SSF is a promising strategy to utilize water hyacinth biomass. Abstract: In this study, bioethanol production from NaOH/H2 O2 -pretreated water hyacinth was investigated. Pretreatment of water hyacinth with 1.5% (v/v) H2 O2 and 3% (w/v) NaOH at 25 °C increased the production of reducing sugars (223.53 mg/g dry) and decreased the cellulose crystallinity (12.18%), compared with 48.67 mg/g dry and 22.80% in the untreated sample, respectively. The newly isolated Kluyveromyces marxianu K213 showed greater ethanol production from glucose (0.43 g/g glucose) at 45 °C than did the control Saccharomyces cerevisiae angel yeast. The maximum ethanol concentration (7.34 g/L) achieved with K. marxianu K213 by simultaneous saccharification and fermentation (SSF) from pretreated water hyacinth at 42 °C was 1.78-fold greater than that produced by angel yeast S. cerevisiae at 30 °C. The present work demonstrates that bioethanol production achieved via SSF of NaOH/H2 O2 -pretreated water hyacinth with K. marxianu K213 is a promising strategy to utilize water hyacinth biomass.